2003
DOI: 10.1002/nme.717
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically based models: Adaptive refinement for B‐spline finite element

Abstract: SUMMARYThis article presents two new methods for adaptive reÿnement of a B-spline ÿnite element solution within an integrated mechanically based computer aided engineering system.The proposed techniques for adaptively reÿning a B-spline ÿnite element solution are a local variant of np-reÿnement and a local variant of h-reÿnement. The key component in the np-reÿnement is the linear co-ordinate transformation introduced into the reÿned element. The transformation is constructed in such a way that the transformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…This procedure can be performed to construct conforming shape functions for quadtree elements with any number of hanging nodes by using the corresponding polygonal reference element. On using this approach there is no need to restrict the number of hanging nodes to one on each edge (2:1 rule) as is needed in some of the other techniques [2,3,[6][7][8]10]. …”
Section: Conforming Interpolants On Quadtree Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure can be performed to construct conforming shape functions for quadtree elements with any number of hanging nodes by using the corresponding polygonal reference element. On using this approach there is no need to restrict the number of hanging nodes to one on each edge (2:1 rule) as is needed in some of the other techniques [2,3,[6][7][8]10]. …”
Section: Conforming Interpolants On Quadtree Meshesmentioning
confidence: 99%
“…Due to the presence of these hanging nodes, incompatibilities arise in classical finite element approximations. Special techniques have been used to construct conforming approximations over quadtree meshes: constraining hanging nodes to corner nodes [1], adding temporary elements to construct a compatible mesh [2,3], Lagrange multipliers and penalty or Nitsche's method to impose constraints [4,5], using hierarchical enrichment [6,7] or B-splines [8], and natural neighbor basis functions [9,10]. In this paper the method developed in Reference [9] is employed to resolve the problem associated with the presence of hanging nodes.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, directly constructing conforming approximations on a quadtree is appealing-the quadtree data structure is untouched and a standard Galerkin formulation suffices with no changes in the properties of the stiffness matrix. The application of B-spline finite elements [27], hierarchical nodal refinement [28,29], and use of natural neighbor basis functions [18,30] are a few approaches that share this viewpoint.…”
Section: Quadtree Meshesmentioning
confidence: 99%
“…In fact, a considerable body of literatures now exists on the application of uniform and non-uniform B spline techniques to the solution of partial differential equations (PDEs) and mechanics problems. The recent studies of B spline method can be found in some articles [17][18][19][20][21][22][23]. The B spline basis functions have compact support and lead to banded stiffness matrices.…”
Section: Introductionmentioning
confidence: 99%